2019
DOI: 10.1016/j.stemcr.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Gain of 20q11.21 in Human Pluripotent Stem Cells Impairs TGF-β-Dependent Neuroectodermal Commitment

Abstract: Summary Gain of 20q11.21 is one of the most common recurrent genomic aberrations in human pluripotent stem cells. Although it is known that overexpression of the antiapoptotic gene Bcl-xL confers a survival advantage to the abnormal cells, their differentiation capacity has not been fully investigated. RNA sequencing of mutant and control hESC lines, and a line transgenically overexpressing Bcl-xL , shows that overexpression of Bcl-xL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 44 publications
2
54
0
Order By: Relevance
“…Both results suggest that there are hurdles in ectodermal lineage commitment in hPSCs due to the CNV gain at 20q11.21. This result is consistent with a recent study that reported that CNV gain at 20q11.21 in hPSCs leads to impaired neuroectodermal differentiation 40 . Markouli et al 40 .…”
Section: Discussionsupporting
confidence: 94%
“…Both results suggest that there are hurdles in ectodermal lineage commitment in hPSCs due to the CNV gain at 20q11.21. This result is consistent with a recent study that reported that CNV gain at 20q11.21 in hPSCs leads to impaired neuroectodermal differentiation 40 . Markouli et al 40 .…”
Section: Discussionsupporting
confidence: 94%
“…This region includes the gene BCL2L1, an antiapoptotic factor that favors clonal outgrowth [40,41]. Notably, this genetic aberration may also impair the differentiation of pluripotent cells [41], and this might explain why iPSCs of donor 1 repeatedly failed to differentiate towards iMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent genetic aberrations in PSCs are not only genotypically similar to those seen in cancer, but the consequential cellular phenotypes are comparable as well. Effects include escaping apoptosis (Avery et al., 2013; Merkle et al., 2017), decreased differentiation capacity (Markouli et al., 2019), increased tumorigenicity (Ben‐David et al., 2014), and faster cell cycling (Barbaric et al., 2014). Therefore, detecting an abnormality can help explain difficulty with a directed differentiation protocol or indicate a newly adopted culture practice as suboptimal.…”
Section: Recurrent Changes In Pluripotent Stem Cellsmentioning
confidence: 99%
“…Current Protocols in Stem Cell Biology capacity (Markouli et al, 2019), increased tumorigenicity (Ben-David et al, 2014), and faster cell cycling (Barbaric et al, 2014). Therefore, detecting an abnormality can help explain difficulty with a directed differentiation protocol or indicate a newly adopted culture practice as suboptimal.…”
Section: Of 11mentioning
confidence: 99%
See 1 more Smart Citation